Martyrdom (Shahīd) in Prophetic Hadiths: A Thematic Study of Classification and Scholarly Interpretation: - Sofyan, Nur Baety (El-Sunan: Journal of Hadith and Religious Studies, 2025)
The purpose of this study is to present a precise and coherent interpretation the meaning of martyr (shahid) both linguistically and within Islamic terminology. It also aims to study the reason for the name “martyr” (shahid), the virtues, and categories of martyr (shahid), as well as the muslim scholarly explanations of the hadiths concerning martyrdom (shahid). This research uses the library research method with a descriptive analytical approach, which involves collecting data, and analysing the perspective of Muslim scholar of the hadith on martyrdom. The study begins by defining martyr (shahid) both linguistically and within Islamic terminology, exploring the reason for the name “martyr” (shahid), its virtues and categories and examining related hadiths along with their narrators, status of hadiths and scholarly interpretations. The result of this study can be summarized into three main points: first: A martyr, according to Islamic law, is one who is killed in the cause of God, meaning one who fights to make the word of God supreme, or one who is killed unjustly outside of combat. Second: Scholars have divided martyrs into three categories: The martyr of this world, The martyr of this world and the Hereafter, and the martyr of the Hereafter. Third: There are textual variations in the wording of the hadiths about martyrdom. Certain reports specify a particular number of categories as martyrs, whereas others indicate different numbers. However, scholars have already explained that the Prophet (peace and blessings be upon him) was informed of the fewest reasons, then he was informed of more, which he mentioned at another time, without intending to limit the number to any one of them and there is no contradiction, for at one time it was revealed to him that they were five, and at another time it was revealed to him that they were more. ABSTRAK Tujuan penelitian ini adalah menyajikan penafsiran yang tepat dan koheren mengenai makna syahid, baik secara linguistik maupun dalam terminologi Islam. Selain itu, penelitian ini bertujuan mengkaji alasan penamaan “syahid”, keutamaan serta klasifikasi syahid, serta penjelasan para ulama Muslim terhadap hadis-hadis yang berkaitan dengan kesyahidan. Penelitian ini menggunakan metode studi kepustakaan (library research) dengan pendekatan deskriptif-analitis, yang dilakukan melalui pengumpulan data dan analisis pandangan para ulama hadis mengenai konsep syahid. Penelitian diawali dengan pembahasan definisi syahid secara bahasa dan istilah, dilanjutkan dengan penjelasan tentang alasan penamaan syahid, keutamaannya, serta klasifikasinya. Selanjutnya, penelitian ini mengkaji hadis-hadis yang berkaitan dengan syahid, termasuk para perawinya, status kesahihan hadis, serta penafsiran para ulama terhadapnya. Hasil penelitian ini dapat dirangkum dalam tiga poin utama. Pertama, syahid menurut hukum Islam adalah seseorang yang terbunuh di jalan Allah, yaitu orang yang berjuang untuk menegakkan kalimat Allah, atau seseorang yang terbunuh secara zalim di luar medan peperangan. Kedua, para ulama membagi syahid ke dalam tiga kategori, yaitu syahid dunia, syahid dunia dan akhirat, serta syahid akhirat. Ketiga, terdapat variasi redaksi dalam hadis-hadis yang menjelaskan tentang syahid. Sebagian riwayat menyebutkan jumlah kategori syahid tertentu, sementara riwayat lain menyebutkan jumlah yang berbeda. Namun, para ulama menjelaskan bahwa Nabi Muhammad ﷺ pada awalnya diberi pengetahuan tentang sejumlah sebab yang terbatas, kemudian pada kesempatan lain diberi pengetahuan tentang sebab-sebab tambahan yang beliau sampaikan pada waktu yang berbeda. Hal ini menunjukkan bahwa penyebutan jumlah tersebut tidak dimaksudkan untuk membatasi kategori syahid pada jumlah tertentu, sehingga tidak terdapat pertentangan di antara hadis-hadis tersebut.